Private transfers and poverty reduction in the United States and France - Rachel Karen (Luxembourg Income Study (LIS), 2023)
Prior research has documented financial transfers between kin and how such assistance often alleviates material hardship, yet few studies have attempted to systematically document the redistributive impact of these transfers. The current study explores the effects of financial transfers on poverty rates using data from the Luxembourg Income Study (LIS) to understand the role of public and private transfers on poverty reduction in the United States and France. This study analyzes poverty outcomes based on (i) market income (income prior to taxes and transfers), (ii) market income plus public transfers, and (iii) income plus private transfers. This disaggregation provides insight into the extent to which public and private transfers reduce market-generated poverty. Results indicate that private transfers can be an important source of household income for American and French families, however, such transfers frequently benefit households who are already at lower risks for poverty. Private transfers are not limited to covering gaps in the safety net but rather reflect one means by which families may confer advantage across generations.
Keywords: 330